2016
DOI: 10.2486/indhealth.2016-0126
|View full text |Cite
|
Sign up to set email alerts
|

Organizational climate with gender equity and burnout among university academics in Japan

Abstract: We investigated relationships between the perception of organizational climate with gender equity and psychological health among 94 women and 211 men in a Japanese private university in 2015 using the Copenhagen Burnout Inventory (i.e., personal, work-related and student-related burnout). Perceptions of organizational climate with respect to gender equity were measured with two scales including organizational engagement with a gender equal society in the workplace (consisting of three domains of ‘Women utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
2
23
0
5
Order By: Relevance
“…Another investigation reported that burnout was directly associated to the number of hours worked. That is, for the outcome of student-related burnout, "work hours" was a significant factors directly associated with burnout scores (Taka et al, 2016). On the other hand, Robins et al (2015) found no statistically significant differences in terms of academic discipline.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Another investigation reported that burnout was directly associated to the number of hours worked. That is, for the outcome of student-related burnout, "work hours" was a significant factors directly associated with burnout scores (Taka et al, 2016). On the other hand, Robins et al (2015) found no statistically significant differences in terms of academic discipline.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, the process of socialization plays a key role, encouraging social dependence in women, and independence associated with the sense of competence in men (Dedovic et al, 2009). The study of Taka et al (2016) suggests that women may be more psychologically vulnerable to the organizational climate for gender inequality than their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comumente, mulheres apresentam maiores níveis de Exaustão Emocional enquanto que os homens, de Despersonalização (Maslach & Leiter, 2016b;Schaufeli, 2017;Shirom, 2003). Todavia, algumas pesquisas sugerem que o tipo de profissão e políticas de respeito a igualdade de gêneros influenciam a não diferenciação dos níveis de burnout entre os dois sexos (Aguayo, Vargas, Cañadas, & De La Fuente, 2017;Puranova, Radostina, & Muros, 2010;Taka et al, 2016).…”
Section: Fatores Sociodemográficosunclassified
“…Como exemplo, há estudos que apontam para uma tendência de homens apresentarem níveis mais elevados de Despersonalização, enquanto mulheres apresentariam maiores níveis de Exaustão Emocional (CAMPOS, 2013;CARLOTTO, 2011;MASLACH;SCHAUFELI;LEITER, 2001). No entanto, é possível serem encontradas pesquisas em que a não diferença estatisticamente significativa dos níveis de burnout pode estar relacionada com a adoção, pela instituição, de políticas de igualdade entre os sexos (TAKA et al, 2016).…”
Section: Introductionunclassified